2012
DOI: 10.1063/1.4723865
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the onset of thermosolutal convection in rotating spherical shells

Abstract: The influence of an externally enforced compositional gradient on the onset of convection of a mixture of two components in a rotating fluid spherical shell is studied for Ekman numbers E = 10−3 and E = 10−6, Prandtl numbers σ = 0.1, 0.001, Lewis numbers τ = 0.01, 0.1, 0.8, and radius ratio η = 0.35. The Boussinesq approximation of the governing equations is derived by taking the denser component of the mixture for the equation of the concentration. Differential and internal heating, an external compositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 25 publications
5
31
0
Order By: Relevance
“…We employ the Boussinesq approximation in that variations in density are assumed important only when affecting the gravitational force −ργr, with γ a constant. In order to isolate the effects induced by differences in thermal and chemical diffusivities we follow (Busse 2002, Net et al 2012) and disregard any differences in source-sink distribution and in boundary conditions for the temperature T and the concentration C. Static profiles T (r) and C(r) with radial gradients ∂ r T = −β T r and ∂ r C = −β C r then exist assuming the temperature and concentration are fixed at the boundaries and have uniformly distributed sources with constant densities β T and β C , respectively.…”
Section: Mathematical Formulation and Numerical Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employ the Boussinesq approximation in that variations in density are assumed important only when affecting the gravitational force −ργr, with γ a constant. In order to isolate the effects induced by differences in thermal and chemical diffusivities we follow (Busse 2002, Net et al 2012) and disregard any differences in source-sink distribution and in boundary conditions for the temperature T and the concentration C. Static profiles T (r) and C(r) with radial gradients ∂ r T = −β T r and ∂ r C = −β C r then exist assuming the temperature and concentration are fixed at the boundaries and have uniformly distributed sources with constant densities β T and β C , respectively.…”
Section: Mathematical Formulation and Numerical Solutionmentioning
confidence: 99%
“…When the instability is driven by the small-diffusivity component it is called fingering; when the instability driven by the large-diffusivity component it is known as diffusive convection; see (Radko 2013). The linear onset in a two-component fluid layer constrained between two horizontal boundaries was studied by (Stern 1960, Nield 1967, Veronis 1968, Baines and Gill 1969 who naturally focussed on the fingering and diffusive regimes. The effect of rotation with respect to a vertical axis was considered by Pearlstein (1981) who found that a non-rotating layer can be destabilized by rotation, and that a rotating layer can be destabilized by the addition of a bottom-heavy solute gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have developed several time integration and stability analysis codes, using this approach, for the convection in spherical shells of pure and binary fluids with very good results [33][34][35][36][37][38]. The main reasons for using collocation methods were simplicity and that changing boundary conditions was easy.…”
Section: Introductionmentioning
confidence: 99%
“…From a mathematical point of view the difficulties of the spherical geometry in the rotating case make the attempts of analytical treatment extremely challenging, requiring very careful sequences of approximations to preserve the relevant features. The tools used to study the problem have been those of hydrodynamic stability theory, to obtain the critical value of the parameters, and the structure of the solutions at the onset of convection by using analytical, semianalytical [1][2][3][4][5][6], or numerical methods [7][8][9][10], and time evolution codes to obtain the nonlinear solutions at low [11][12][13] or high supercritical Rayleigh numbers [14][15][16][17], to mention just a few of all the available references.…”
Section: Introductionmentioning
confidence: 99%